The Effects of War-Related Stress on Human Development: Differences in Body Proportions of Polish Women Born Before and During World War II - Koníková, Linda; Liczbińska, Grażyna; Králík, Miroslav (American journal of human biology, 2025)
OBJECTIVES: This study aims to explore the lasting effects of stress experienced by pregnant women during World War II (WWII) on body and head measurements of their adult daughters. METHODS: The research sample consists of 336 female university students born in Poland between 1925 and 1951. The data include body measurements and socioeconomic information (parental occupation and number of siblings) acquired from questionnaires collected between the 1950s and 1970s. Student's t-test, Mann-Whitney test and Analysis of Variance were used to analyze differences in body measurements between groups of women born before and during the war, as well as the possible influences of socioeconomic variables. RESULTS: The mean measurements of body height, symphysion height, and waist circumference were lower in women conceived and born during the war compared to those born in the pre-war period. In contrast, the mean measurements of biacromial (shoulder) width, trunk length, and three head dimensions were higher in women conceived and born during the war. Additionally, the number of siblings appeared to be a significant factor that may have influenced the body measurements of women in both groups. For instance, a higher number of living siblings, particularly sisters, was associated with reduced body dimensions, such as body height and waist circumference, while a greater number of deceased siblings was linked to an increase in certain body dimensions. CONCLUSION: The results suggest that war-related prenatal conditions may have influenced the postnatal growth and development of women conceived and born during the war. Notably, the direction of these changes varied, which indicates that the growth response to the war-related conditions was a complex adaptation, reflecting both positive and negative changes in different body parts, rather than a uniform pattern of growth suppression.
Keywords: Socioeconomic Factors; Young Adult; Poland; psychický stres; Pregnancy; Stress, Psychological; těhotenství; Adult; World War II; socioekonomické faktory; dospělí; lidé; Female; ženské pohlaví; Polsko; Humans; mladý dospělý; 2. světová válka